The Future of the South China Sea - Kim, Jiye (University of Michigan Press, 2026)
For over seventy years, China has steadfastly asserted its sovereignty over the South China Sea, transforming these waters into a flashpoint of international tension and a focal point of global diplomacy. The Future of the South China Sea intricately explores China’s motivations, unveiling its ambitions in the South China Sea that are anything but static. Despite the prevailing narrative that frames China’s objectives as monolithic and unchanging, its underlying interests in the region have fluctuated in both content and urgency, driven by economic imperatives, historical legacies, domestic pressures, and broader international security concerns. By incorporating negotiation records, such as the 1958 Declaration on China’s Territorial Sea, the 1992 ASEAN Declaration, and the 2005 Tripartite Agreement, Jiye Kim traces how China reshapes its interests into negotiation agendas, providing critical insights into the nation’s diplomacy and making a significant contribution to an existing literature on the South China Sea that has been largely dominated by analyses of great power rivalry. This book sheds light on China’s underlying interests as living and adaptable entities, providing scholars with a detailed, evidence-based understanding of the complexities that define one of the world’s most contested maritime regions.